The Therapy Spiritual Emotional Freedom Technique (SEFT) Towards Anxiety In The Elderly At Rw 14 Kelurahan Solokpandan-Kabupaten Cianjur - Budiman, .; Badrujamaludin, Asep; Ahdiyatunnisa, Hafsa (KnE Life Sciences, 2021)
The total elderly population (over 60 years old) in West Java in 2017 was 4.16 million. Factors which effect anxiety experienced by the elderly include bad memories. One way to decrease anxiety is SEFT therapy, that is a healing technique combining psychology and spiritual power. This research aims to evaluate the effect of SEFT therapy on anxiety amongst the elderly. The research used quasi experiment methods with pre-test post-test and a non-probability sampling technique with purposive sampling method, which obtained with 38 respondents of which 19 received SEFT therapy six times in a week and 19 were the control group. The results of this research shows an average anxiety level in the treatment group before intervention of 29.74 with standard deviation of 11.435 and after intervention this dropped to 20.79 with a standard deviation of 6.997. Within the control group, the average of anxiety level before was 26.58 with standard deviation 9.640 and after was 26.32 with standard deviation 8.564. The statistical test uses parametric test, which is paired t-test analysisi which shows that there are differences in the average anxiety level after intervention in both groups with p value 0.036 (α ≤0.05). Based on the results it can be concluded that SEFT improved anxiety level significantly in the elderly. Therefore, the SEFT therapy can be applied in the community as an alternative therapy to overcome anxiety. Keywords: SEFT Therapy, Elderly, Anxiety